2012
DOI: 10.1155/2012/416138
|View full text |Cite
|
Sign up to set email alerts
|

Association of the PGC-1αrs8192678 Variant with Microalbuminuria in Subjects with Type 2 Diabetes Mellitus

Abstract: PPAR-γ co-activator-1α (PGC-1α) is a tissue-specific transcriptional co-activator involved in the regulation of antioxidant enzymes. The A-allele of the rs8192678 PGC-1 α} (G>A) gene variant has previously been associated with nephropathy in Korean and Indian-Asian type 2 diabetes mellitus (T2DM) samples. Our aim was to examine the association between this variant and urine albumin exccretion in European subjects with T2DM. Genotyping was performed on 583 European subjects with T2DM and examined in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Sakamoto et al [50] found YKL-40 levels were significantly elevated in type 1 diabetic patients than in healthy controls and demonstrated YKL-40 levels were a determinant of ACR independent of other risk factors. Prior et al [55] found a significant association between genotype (GG/GA/AA) and urinary albumin (normoalbumuria vs. micro/macroalbuminuria, p = 0.01). Mashima et al [56] single nucleotide polymorphisms (SNPs) in six proinflammatory cytokine genes IL-6 and CCL1 genes were associated with albuminuria and the combination of these genotypes had an additive effect on the prevalence and severity of albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…Sakamoto et al [50] found YKL-40 levels were significantly elevated in type 1 diabetic patients than in healthy controls and demonstrated YKL-40 levels were a determinant of ACR independent of other risk factors. Prior et al [55] found a significant association between genotype (GG/GA/AA) and urinary albumin (normoalbumuria vs. micro/macroalbuminuria, p = 0.01). Mashima et al [56] single nucleotide polymorphisms (SNPs) in six proinflammatory cytokine genes IL-6 and CCL1 genes were associated with albuminuria and the combination of these genotypes had an additive effect on the prevalence and severity of albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α), consists a transcriptional co-activator, which mainly regulates mitochondrial biogenesis and contributes to antioxidant defense mechanisms (Qi et al, 2015). Gly482Ser SNP has been associated with a decreased gene expression and a reduction in the activity of PCG-1α (Prior et al, 2012). ALS carriers of the Gly482Ser polymorphism show increased exercise-related oxidative stress, despite the lack of strong evidence of association between Gly482Ser and ALS (Pasquinelli et al, 2016).…”
Section: Sod1 Hfe Transferrin Gsts Pgc-1α and Nrf2mentioning
confidence: 99%
“…However, there is no unified diagnostic standard associated with the HbA1c detection method, which does not represent the current blood glucose level and easily results in misdiagnosis (Vajravelu and Lee, 2018). Genetic testing methods are varied and are selected according to particular requirements, but there are still legal and social ethics issues (Etchegary et al, 2010;Prior et al, 2012). Glucose tolerance test (OGTT) methods have the advantages of objectivity and accuracy, which is the "gold standard" for the diagnosis of pre-diabetes.…”
Section: Introductionmentioning
confidence: 99%